Incorporating peer recording in blended learning execution for low proficiency English learners: practice for role-play assessment / Siti Zarikh Sofiah Abu Bakar, Fairuz Husna Mohd Yusof and Diana Othman - Abu Bakar, Siti Zarikh Sofiah; Mohd Yusof, Fairuz Husna; Othman, Diana (2018)
Blended learning has been significantly applied in most courses and subjects offered in Malaysian Higher Education Institutions including Universiti Teknologi Mara (UiTM) Malaysia. One of the 21st century teaching and learning method practised is peer recording with the involvement of social networking site for role play preparation. Since these low English proficiency students are currently struggling to practise the language, peer recording is expected to assist them in role play preparation. However, the effectiveness of peer recording is dubious as the recording is produced without the presence of the lecturers. Therefore, this study investigates the effectiveness of using peer recording as a technique in practising for role play assessment, while supporting the execution of blended learning among low proficiency English learners. A qualitative approach was used to obtain the data, which is open-ended question interview. This study used purposive sampling involving 11 Pre-Diploma (UiTM) who are required to upload their role play practice videos on class Facebook Group for their peers to comment. They were interviewed by using the open-ended questions to gain their explanation on their confidence and fluency improvement after practising using peer recording technique. Data collected were analysed by using content analysis. The comparison of marks for role play practice (peer recording) and role play (assessment) was also carried out to obtain remarkable difference of those two. Findings have shown great improvement in terms of students' confidence (80%) and fluency (50%) for role play assessment.